2023
DOI: 10.1007/s15010-023-02013-y
|View full text |Cite|
|
Sign up to set email alerts
|

Patient characteristics in sepsis-related deaths: prevalence of advanced frailty, comorbidity, and age in a Norwegian hospital trust

Abstract: Objective To examine the prevalence of advanced frailty, comorbidity, and age among sepsis-related deaths in an adult hospital population. Methods Retrospective chart reviews of deceased adults within a Norwegian hospital trust, with a diagnosis of infection, over 2 years (2018–2019). The likelihood of sepsis-related death was evaluated by clinicians as sepsis-related, possibly sepsis-related, or not sepsis-related. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The CCI, developed in 1987, is considered the gold standard for assessing comorbidities in clinical studies [ 32 ], as a tool used to predict long-term mortality in patients [ 33 ]. Previous studies have also shown an increase in patient mortality with increasing CCI [ 34 , 35 ], consistent with our results. We usually use the GCS which is a scale used to assess a patient’s level of consciousness [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…The CCI, developed in 1987, is considered the gold standard for assessing comorbidities in clinical studies [ 32 ], as a tool used to predict long-term mortality in patients [ 33 ]. Previous studies have also shown an increase in patient mortality with increasing CCI [ 34 , 35 ], consistent with our results. We usually use the GCS which is a scale used to assess a patient’s level of consciousness [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…We accept that there may be an age-related selection bias for admissions to a specialist cardiology ward. Older patients who present with cardiac arrest usually have an underlying coronary artery disease, whereas younger patients tend to have structural heart disease and/or arrhythmogenic disorders [ 22 , 23 , 24 , 25 ]. Out of these young patients, there was one cardiac arrest event that resulted in death in whom arrhythmogenic right ventricular cardiomyopathy was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have focused on precisely characterizing the specific preexisting chronic conditions responsible for enhancing the mortality risk of sepsis. [4,8,14] One study found that the second most common cause of mortality in patients with sepsis is due to chronic heart disease (15.3%), but the exact type of chronic heart disease was not specified. [4] Coronary artery disease (CAD), an atherosclerotic disease that involves the buildup of plaque in the vessel walls and narrowing of the coronary arteries that supply the heart muscle, is the most common form of chronic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on precisely characterizing the specific preexisting chronic conditions responsible for enhancing the mortality risk of sepsis. [4,8,14] One study found that the second most common cause of mortality in patients with sepsis is due to chronic heart disease (15.3%), but the exact type of chronic heart disease was not specified. [4]…”
Section: Introductionmentioning
confidence: 99%